1998
DOI: 10.1021/bi972818b
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Oxidized Fe7S8 Ferredoxin from the Thermophilic Bacterium Bacillus schlegelii by 1H NMR Spectroscopy,

Abstract: The solution structure of the paramagnetic seven-iron ferredoxin from Bacillus schlegelii in its oxidized form has been determined by 1H NMR. The protein, which contains 77 amino acids, is thermostable. Seventy-two residues and 79% of all theoretically expected proton resonances have been assigned. The structure has been determined through torsion angle dynamics calculations with the program DYANA, using 966 meaningful NOEs (from a total of 1305), hydrogen bond constraints, and NMR derived dihedral angle const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 68 publications
3
40
0
Order By: Relevance
“…Bs ferredoxin is known to be a thermostable protein. Temperature-dependent NMR studies on the WT showed that the protein can be heated up to 90°C for at least 15 min without appreciable denaturation or loss of the iron-sulfur clusters [11]. An analogous experiment was performed under anaerobic conditions on D13C, which was kept at 90°C for more than 25 min without noticeable denaturation (data not shown).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Bs ferredoxin is known to be a thermostable protein. Temperature-dependent NMR studies on the WT showed that the protein can be heated up to 90°C for at least 15 min without appreciable denaturation or loss of the iron-sulfur clusters [11]. An analogous experiment was performed under anaerobic conditions on D13C, which was kept at 90°C for more than 25 min without noticeable denaturation (data not shown).…”
Section: Resultsmentioning
confidence: 87%
“…The structure calculations were carried out according to a recently developed torsion angle dynamics (TAD) approach using the program DYANA [20] as described earlier for the WT [11]. As in the latter case, they were supplemented by restrained energy minimization (REM) on the 20 structures of the DYANA family with the lowest target function values followed by restrained molecular dynamics (RMD) in vacuo.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations